Antibiotic resistance of pathogenic Acinetobacter species and emerging combination therapy - Shin, Bora; Park, Woojun (The journal of microbiology, 2017)
The increasing antibiotic resistance of Acinetobacter species in both natural and hospital environments has become a serious problem worldwide in recent decades. Because of both intrinsic and acquired antimicrobial resistance (AMR) against last-resort antibiotics such as carbapenems, novel therapeutics are urgently required to treat Acinetobacter -associated infectious diseases. Among the many pathogenic Acinetobacter species, A. baumannii has been reported to be resistant to all classes of antibiotics and contains many AMR genes, such as bla ADC ( Acinetobacter -derived cephalosporinase). The AMR of pathogenic Acinetobacter species is the result of several different mechanisms, including active efflux pumps, mutations in antibiotic targets, antibiotic modification, and low antibiotic membrane permeability. To overcome the limitations of existing drugs, combination theraphy that can increase the activity of antibiotics should be considered in the treatment of Acinetobacter infections. Understanding the molecular mechanisms behind Acinetobacter AMR resistance will provide vital information for drug development and therapeutic strategies using combination treatment. Here, we summarize the classic mechanisms of Acinetobacter AMR, along with newly-discovered genetic AMR factors and currently available antimicrobial adjuvants that can enhance drug efficacy in the treatment of A. baumannii infections.